Assessing Food Insecurity in Latin America and the Caribbean Using FAO’s Food Insecurity Experience Scale - Smith, Michael D.; Kassa, Woubet; Winters, Paul (Elsevier, 2018)
The complexity of the operational concept and definition of food insecurity has complicated the study of the ‘food insecure’ and efforts to determine clear policy directions. Previous findings on the prevalence and severity of food insecurity are inconsistent and often depend on the measure used. To overcome limitations in food security measurement, the Food and Agriculture Organization of the United Nations developed the Food Insecurity Experience Scale, which is the first survey protocol to measure people’s direct experience of food insecurity on a global scale. Using this new measure, our study contributes to the understanding of the food insecure by examining the determinants of food insecurity within and across countries in Latin America and the Caribbean (LAC). Using a series of multilevel linear models, we find the three determinants associated with the largest increase in the likelihood of experiencing food insecurity in LAC are: low levels of education, limited social capital, and living in a country with low GDP per capita. Results suggest the need to promote education of the most vulnerable, encourage social interactions that help build individuals’ social capital, and adopt gender-sensitive programs. The results also suggest the need for a shift in policy from short-term strategies to long-term efforts that sustain household productive capacity and employment to promote sustained economic growth.